2013
DOI: 10.1016/j.exphem.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A germline point mutation in Runx1 uncouples its role in definitive hematopoiesis from differentiation

Abstract: Definitive hematopoiesis requires the master hematopoietic transcription factor Runx1, which is a frequent target of leukemia-related chromosomal translocations. Several of the translocation-generated fusion proteins retain the DNA binding activity of Runx1, but lose subnuclear targeting and associated transactivation potential. Complete loss of these functions in vivo resembles Runx1 ablation, which causes embryonic lethality. We developed a knock-in mouse that expresses full length Runx1 with a mutation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…TP53 mutation is independently associated with a poor prognosis, more frequently with complex karyotypes (50%) and del(5q) (15%‐20%), and may predict resistance or relapse to lenalidomide in MDS patients 4 . However, different degrees of gene mutations lead to different clinical phenotypes 26 . The clinical relevance of VAF for the majority of mutations is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 mutation is independently associated with a poor prognosis, more frequently with complex karyotypes (50%) and del(5q) (15%‐20%), and may predict resistance or relapse to lenalidomide in MDS patients 4 . However, different degrees of gene mutations lead to different clinical phenotypes 26 . The clinical relevance of VAF for the majority of mutations is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the recognized role in hematopoiesis and hematological malignancies [22,[27][28][29][30][31][32][33][34][35][36][37][38][39], RUNX1 has been recently identified as a key player in breast cancer development and tumor progression [40][41][42][43][44][45][46][47]. Findings from our group [48], reinforced by studies from others [49,50], have shown that RUNX1 plays a critical role in maintaining breast epithelial phenotype and prevents EMT.…”
Section: Introductionmentioning
confidence: 63%
“…We have shown that RUNX proteins reside in punctate subnuclear domains and their subnuclear localization is functionally linked with transcriptional activity [30,[82][83][84][85][86][87][88][89][90][91][92][93][94]. To investigate subcellular localization of RUNX1 in normal mammary epithelial cells, we performed immunofluorescence (IF) microscopy in actively proliferating MCF10A cells and imaged cells in interphase as well as those undergoing spontaneous mitoses.…”
Section: Runx1 Organizes As Punctate Foci In the Mammary Epithelial Cmentioning
confidence: 99%
“…Our results suggest that RUNX1 is a target for positive regulation by RUNXOR. The RUNX1 gene is a Runt-related transcription factor, also known as AML1 (acute myelogenous leukemia 1), that regulates the expression of several important hematopoietic regulator genes [ 50 , 51 , 52 , 53 , 54 ], including genes regulating B-cell maturation [ 55 ], granulocyte differentiation, and megakaryocyte maturation [ 56 ]. The RUNX1 gene is frequently mutated in various hematological malignancies [ 57 ].…”
Section: Discussionmentioning
confidence: 99%